If 3x equals 72 then you would have to take 3x divided by three and 72 divided by 3 because you have to do it to the same side. So if 3x=72 then x would equal 24.
Rearrange the equation to read : y = 6 - 3x and graph normally.
Sensible but hard to explain
I don't understand your question but y=3x is the function of a graph, to graph the function you would plug points into the function such as x=0, x=1, x=-1 and you would find the y values at each point so that you can graph it. In this case the graph is a parabola which has a u shape.
y = 3x =3(6) = 18 ... the ordered pair is (x,y) = (6,18)
First of all, if 'x' is 3, then 'x' doesn't equal -3x+3 . You must mean y = -3x + 3.If x=3, then (-3x + 3) = -6 .The graph is the point (3, -6) .
3x - 9y = 27-9y = -3x + 279y = 3x - 27y = x/3 - 3The graph is a straight line, with (slope = 3), and passing through the point (y = - 3) on the y-axis.